HUBUNGAN PENGETAHUAN DAN SIKAP IBU DENGAN TINDAKAN PEMBERIAN ASI EKSKLUSIF DI PUSKESMAS RAMBUNG KECAMATAN BINJAI SELATAN KOTA BINJAI TAHUN 2017 - Nurleli Nurleli; Jenny Marlindawani Purba; Rinawati Sembiring (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2018)
Exclusive ASI (breast milk) is breastfeeding with only breast milk, without giving other supplements like orange juice, honey, tea, or plain water and without other solid food like banana, milk porridge, biscuit, rice porridge, and rice cooked in a pan of water (au bain-marie). It is the best food for the survival of a 0-6 month-old baby, and it is better to continually give until the baby is 2 years old. The objective of this research was to find out the correlation of women’s knowledge and attitude with breastfeeding with exclusive ASI. The research used observational analytic method with sectional design. The population was 687 women who breastfed their 6-12 month-old babies at Rambung Puskesmas, and 90 of them were used as the samples, taken by using consecutive sampling technique and Lame show formula. The data were analyzed by using chi square test at the significance level of 95% (0.05). The result of the research showed that there was significant correlation of the respondents’ knowledge (p<0.05) and attitude (p<0.05) with breastfeeding with exclusive ASI. It could be concluded that education was closely related to knowledge, attitude, and action in breastfeeding with exclusive ASI. It is recommended that the Head of Rambung Puskesmas, Binjai Selatan Subdistrict increase health promotion by socializing the importance of exclusive ASI for babies so that women can improve their knowledge of breastfeeding with exclusive ASI maximally.Keywords: Knowledge, Attitude, Action, Breastfeeding with Exclusive ASI